Migration Impact of Behavioral Science in Organizational Behavior: Empirical Evidence - Connie Shin @ Connie Cassy Ompok; Huazhang Liu; Youjun Ma (Transnational Press London, 2024)
Behavioral science has become a key topic among businesses seeking to tackle the issues that are inherent in decision making processes and organizational behaviors within today’s business environment. This field is an amalgamation of various different sub-disciplines having a shared focus on human behavior. The focus of this study is on ‘nudging’, which is a cost-effective behavioral science approach toward influencing behaviors and prompting better choices and decisions. The nudging concept has been adopted by various organizations across the world. One key issue related to this approach is the difficulties associated with repeatedly delivering personalized, pertinent, and inspiring messages to the multitude of workers within firms. Typically, behavioral data are not available within businesses’ data warehouses and to glean any insights regarding this, workers need to be studied. To tackle this issue, the current study utilized a survey scale which differs from the commonly used Likert scale. Personalized dashboards were delivered to managers and workers by means of the Artificial Intelligence (A.I.) medium. The dashboards used in the study involved organization-wide questionnaires, together with set targets, driven by A.I. Identical questionnaires and dashboards were delivered twice to matching respondents within a single firm. Nudging was not involved in the initial phase, and in the second delivery, the dashboards also included e-mail nudges which served to guide the participants on how to use their dashboards. The click rate showed a 41 % increase during the second delivery, with a 21 % increase of viable clicks. Viable clicks here being interpreted as respondents viewing the dashboard pages and initiating some form of action.